PRIORITIZATION OF CRITERIA FOR PRODUCTION PLANNING SOFTWARE SELECTION USING PICTURE FUZZY PIPRECIA METHOD: A CASE OF THE ORDU PROVİNCE - KORUCUK, Selçuk; AYTEKİN, Ahmet (Journal of process management and new technologies, 2025)
With technological transformation, businesses have begun to carry out more effective production planning and have increasingly needed production planning software programs for short-, medium-, and long-term planning activities. Research shows that production planning software provides significant benefits to businesses in various operational areas such as time management, workforce allocation, production scheduling, overtime control, and inventory management. In addition to enhancing operational efficiency, these software systems also contribute to reducing costs, using resources more effectively, and improving overall organizational performance. However, determining the criteria used in selecting the most suitable production planning software is crucial and requires careful consideration. Within the scope of this study, the criteria used in production planning software selection in manufacturing enterprises were identified and prioritized. For this purpose, the Picture Fuzzy PIPRECIA method was applied. According to the analysis results, among the criteria used in selecting production planning software in manufacturing enterprises, the most important criteria were identified as “Security” and “Reporting and Analysis,” while the least important criteria were found to be “Support and Training” and “Updating and Maintenance.